60Co gamma irradiation effects on GaN quasi-vertical Schottky barrier diodes with passivation layer and their post-irradiation annealing behavior. (1st April 2023) - Song, Xiufeng; Zhang, Jincheng; Wu, Yinhe; Zhao, Shenglei; Du, Lin; Feng, Qi; Zhang, Weiwei; Wang, Zhongxu; Wu, Feng; Liu, Shuang; Liu, Zhihong; Hao, Yue
Abstract: In this work, the effect of gamma irradiation on the quasi-vertical GaN Schottky barrier diodes with a passivation layer was investigated for the first time. The forward I–V characteristic was improved and the reverse leakage was slightly increased after 1 Mrad gamma irradiation. Moreover, the annealing process was carried out after the irradiation. The leakage current was recovered while the forward current continued to increase after the annealing. Then a possible mechanism based on the effect of gamma irradiation on passivation film was proposed to explain the annealing behavior of the passivated device.